Electroanalytical study of the pesticide ethiofencarb - Barroso, M. Fátima (2013)
A detailed study of voltammetric behavior of ethiofencarb (ETF) is reported using glassy carbon electrode (GCE) and hanging mercury drop electrode (HMDE). With GCE, it is possible to verify that the oxidative mechanism is irreversible, independent of pH, and the maximum intensity current was observed at +1.20 V vs. AgCl/Ag at pH 1.9. A linear calibration line was obtained from 1.0x10-4 to 8.0x10-4 mol L-1 with SWV method. To complete the electrochemical knowledge of ETF pesticide, the reduction was also explored with HMDE. A well-defined peak was observed at –1.00V vs. AgCl/Ag in a large range of pH with higher signal at pH 7.0. Linearity was obtained in 4.2x10-6 and 9.4x10-6 mol L-1 ETF concentration range. An immediate alkaline hydrolysis of ETF was executed, producing a phenolic compound (2-ethylthiomethylphenol) (EMP), and the electrochemical activity of the product was examined. It was deduced that it is oxidized on GCE at +0.75V vs. AgCl/Ag with a maximum peak intensity current at pH 3.2, but the compound had no reduction activity on HMDE. Using the decrease of potential peak, a flow injection analysis (FIA) system was developed connected to an amperometric detector, enabling the determination of EMP over concentration range of 1.0x10-7 and 1.0x10-5 mol L-1 at a sampling rate of 60 h-1. The results provided by FIA methodology were performed by comparison with results from high-performance liquid chromatography (HPLC) technique and demonstrated good agreement with relative deviations lower than 4%. Recovery trials were performed and the obtained values were between 98 and 104%.